Complex Scapular Winging following Total Shoulder Arthroplasty in a Patient with Ehlers-Danlos Syndrome - John G. Skedros; Colton M. Phippen; Tanner D. Langston; Chad S. Mears; Amy L. Trujillo; Robert M. Miska (Case Reports in Orthopedics)
This is a unique case of a female patient with features of classical and hypermobile types of Ehlers-Danlos syndrome (EDS) who developed complex scapular winging from spinal accessory and long thoracic neuropathies. These neurological problems became manifest after an uncomplicated total shoulder arthroplasty (TSA). The patient had a complex postoperative course with extensive work-up in addition to revision shoulder surgery and manipulations to treat shoulder stiffness. It was eventually suspected that the periscapular nerve impairments occurred during physical therapy sessions after her TSA. This interpretation was further supported by genetic evidence that, in addition to EDS, the patient had an unrecognized genetic propensity for nerve palsies from stretch or pressure (“hereditary neuropathy with liability to pressure palsies” (HNPP)). By two years after the TSA the neuropathies had only partially improved, leaving the patient with persistent scapular winging and shoulder weakness. With this case we alert surgeons and physical therapists that patients with EDS can have not only a complicated course after TSA, but rare concurrent conditions that can further increase the propensity of neurological injuries that result in compromised shoulder function.